Assessment of agile supply chain practices towards performance of health care sector, in Tanzania: A case of selected public hospitals in Dodoma Municipality - Mwaiseje, Shadrack (Mzumbe University, 2024)
A dissertation Submitted in Partial Fulfillment of the Requirement for the Award of the Degree of Master of Science in Procurement and Supply Chain Management (Msc- PSCM) of Mzumbe University. 2018